TERAMPIL MENULIS ARTIKEL ILMIAH BAGI GURU SEKOLAH DASAR DAN PRAKTISI DI NAGARI KOTO LAWEH KECAMATAN LEMBANG JAYA KABUPATEN SOLOK - Zona Rida Rahayu; Elan Halid; Mega Putri; Rini Wirasty. B; Redo Andi Marta (PUAN INDONESIA, 2023)
Teachers must perpetually develop their professionalism through professional development activities, scientific publication being one of them. This is stated in Law No. 20 of 2003 on the National Education System, Law No. 14 of 2005 on Teachers and Lecturers, Government Regulation No. 19 of 2005 on National Education Standards, and Minister of State Apparatus Empowerment and Bureaucratic Reform Regulation No. 16 of 2009 on the Functional Position of Teachers and their Credit Scores, dated November 10, 2009. Therefore, teachers require writing instruction to prepare them to compose and publish scientific articles. This workshop on the composition of scientific articles was held in Nagari Koto Laweh, Lembang Jaya District, Solok Regency. In their respective professions, teachers and practitioners encounter similar challenges. In the practitioner's world, hierarchical structures and positions, such as supervisors, managers, and others, have their respective benefits. In addition, there are tiers of competence in the field of education that correspond to their respective benefits. Practitioners are typically monitored and required by superiors, whereas in the world of educators, particularly lecturers, there is a hierarchical structure, but lecturers are, in fact, their own managers, including when it is time for promotion. In this study, participant problems include requiring every teacher to publish articles in accredited journals. The Community Partnership Program includes 20 participants: classroom teachers, subject teachers, "bundo kanduang" (local cultural teacher), and staff members. Each participant in the Community Partnership Program has grasped the correct procedure for analyzing scientific articles.